Four new freshwater crab species of the genus Megapleonum Huang, Shih & Ahyong, 2018 (Crustacea, Decapoda, Potamidae) from Guangdong, China - Chao Huang; Hsi-Te Shih; Shane T. Ahyong (ZooKeys)
Four new species of the poorly known genus Megapleonum Huang, Shih & Ahyong, 2018, are described from Guangdong Province, China: Megapleonum falx sp. nov. from Huizhou City, M. yangdongense sp. nov. from Yangjiang City, and both M. ferrumequinum sp. nov. and M. wangjiani sp. nov. from Maoming City. These four new species are all morphologically and genetically distinct from each other and the two known congeners Megapleonum ehuangzhang Huang, Shih & Ahyong, 2018 and Megapleonum shenzhen Huang & Mao, 2021. The extremely divergent morphology of the gonopod 1 of these species alone immediately sets them apart, but there are also distinct differences in other characters, including the carapace, ambulatory leg, and maxilliped 3 exopod flagellum. A phylogeny constructed using the mitochondrial 16S rDNA reveals that all species of Megapleonum form a deep-rooted monophyletic group with significant interspecific genetic distances, supporting the generic placement and specific treatments of these new taxa. A key to the species of Megapleonum is also provided.